La tecnica CATI: dalla ricerca di mercato alla ricerca a buon mercato - Rosa Di Gioia (Quaderni di Sociologia, 2010)
In the past few years the CATI technique has been extensively used in many areas of both social and economic research. As a result of tight deadlines imposed by purchasers together with increased attention to costs and a lack of attention towards methodology, a number of practical flaws emerged in addition to the theoretical constraints that have already been analysed and found within literature, with repercussions on the quality of data.The use of pseudo-panel, the complete delegation of data collection and control phases and the sub-contracting of interviews to foreign laboratories are only some of the strategies adopted by public and private institutions to reduce the costs of research, often at the expense of the quality of research itself.The result is that the distinction between research with commercial aims (typically with low methodological standards) on the one hand, and research carried out for theoretical and academic purposes, on the other, is slowly fading away.